Flexible bronchoscopy via the laryngeal mask: a new technique. Issue 2 (February 1991) - McNamee, C J; Meyns, B; Pagliero, K M
Abstract : Malignant tracheal tumours often cause airway obstruction and this may be aggravated by vocal cord paralysis due to invasion of the recurrent laryngeal nerve. Conventional endoscopic techniques performed under general anaesthesia do not give a simultaneous view of vocal cord function and the distal airways. The technique of bronchoscopy via the laryngeal mask allowed full assessment of the cause of stridor in a patient with a malignant tracheal tumour that was causing airways obstruction and vocal cord paralysis.